2009
DOI: 10.1002/j.2161-1912.2009.tb00098.x
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Antiracism in Counselor Training: Reflections on a Course

Abstract: this article provides a descriptive review of an antiracism course taught within a counseling and development program. adopting a reflective stance, the article presents the rationale for antiracism training, describes the course structure and content, and includes personal reflections from students and the instructor. este artículo proporciona una crítica descriptiva de un curso de antiracismo que se enseñó dentro de un programa de consejería y desarrollo. adoptando una postura de reflexión, el artículo prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…The research team did not anticipate the strength of this "flip" for students. Pieterse (2009) reported that most instruction toward antiracism has been targeted toward White students and indicated that students of color may have different needs. This research supports Pieterse's assertions and indicates that indeed, in planning immersion courses and in evaluating their outcomes, the needs of students belonging to different cultural groups should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The research team did not anticipate the strength of this "flip" for students. Pieterse (2009) reported that most instruction toward antiracism has been targeted toward White students and indicated that students of color may have different needs. This research supports Pieterse's assertions and indicates that indeed, in planning immersion courses and in evaluating their outcomes, the needs of students belonging to different cultural groups should be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of racism can be insidious in that the nature of racism might not be apparent to those who are being affected by it. Given that counselors usually work with clients to find a framework through which they can understand their life experiences, we consider it critical for counselors themselves to be familiar with the manner in which racism operates within American society (Pieterse, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have long called for counselor education programs to address concerns of multicultural and social justice competence in training (e.g., Pack‐Brown, Coulter, & Fuller, ). Consequently, programs have focused on enhancing trainees’ multicultural competence (American Counseling Association, ; Council for Accreditation of Counseling and Related Educational Programs [CACREP], ), with scholars examining multicultural content such as racism and White privilege (e.g., Pieterse, ; Rothman, Malott, & Paone, ). Counselor educators’ focus on these concepts is typically designed to help either White students develop a greater awareness or trainees examine these constructs in society at large (Pieterse, ; Rothman et al, ).…”
mentioning
confidence: 99%
“…Consequently, programs have focused on enhancing trainees’ multicultural competence (American Counseling Association, ; Council for Accreditation of Counseling and Related Educational Programs [CACREP], ), with scholars examining multicultural content such as racism and White privilege (e.g., Pieterse, ; Rothman, Malott, & Paone, ). Counselor educators’ focus on these concepts is typically designed to help either White students develop a greater awareness or trainees examine these constructs in society at large (Pieterse, ; Rothman et al, ). Unfortunately, there has been less attention to the multicultural and social justice inequities of marginalized students (e.g., students of color; lesbian, gay, bisexual, transgender, and queer [LGBTQ] students) within counselor education training programs (Barcus & Crowley, ; Dickson, Argus‐Calvo, & Tafoya, ; Gomez, Khurshid, Freitag, & Lachuk, ; Haizlip, ; Haskins et al, ; Hernández, Almeida, & Carranza, ; West‐Olatunji & Goodman, ).…”
mentioning
confidence: 99%